The Effect of Price Changes on Maize Farmers in Uganda: A Case Study of Kigando Sub-County Kyankwanzi District. - Twizukye, Juliet (Kabale University, 2024)
The study examined the effects of price changes on the welfare of maize farmers in Kigando Sub county, Kyankwanzi district Uganda. The study used 80 as respondents and sample size. The study used descriptive research design by basing on qualitative and quantitative approach in order to get better analysis of the study. Both primary and secondary data collection tools were used with their relevant tools like questionnaire and interview guide in order to come up with required data. In the findings it was established that high costs of production increases the price of my produce which in turn leads to improved welfare. Since the price of maize will be determined by what was put in to be produced. Price fluctuations do not affect my welfare at all. From the findings, some respondents responded that they plan the amount to produce depending on previous price fluctuations, since some will depend on the previous price for them to plan for the next production. Most respondents replied yes on government regulating the prices of agricultural produce to improve income of farmers in the area. The study concludes that the effect of a rise in maize on disposable income is largely mixed. Rises in maize price worsen the welfare of a great proportion in both villages. When the production structure adapts to the price changes, possibilities for welfare gains appear for some specific household categories. The households that earn their livelihood from agriculture, as self-employed farmers, will be able to appropriate wider marketing margins. The study recommends that the government and policymakers in the maize subsector should initiate a package of changes to elicit a better response from both maize producers and consumers. These include but are not limited to the removal of bottlenecks in maize pricing by promoting effective maize market reforms. Once the Ugandan market channels and prices are freed, private traders can then bid up formally depressed maize prices. Under positive price elasticity of supply, higher prices would then induce higher production. This will, in turn, have a positive effect of enabling maize producers to get higher incomes hence increasing their welfare.